Pesticide use and environmental contamination a study in Khao Koh District, Phetchabun Province, Thailand - Piraya Aungudornpukdee (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - The purpose of this paper is to explore environmental contamination from pesticide use in a Khao Kho Sub-district, Khao Kho District in Phetchabun Province, Thailand. Design/methodology/approach - The study area was made up of four villages: Kanok Ngam, Lao Lue, Lao Neng and Phet Dam, all mostly highland areas whose inhabitants are mainly from the hill tribes. The 548 participants were recruited with inclusion criteria being that they must be living in the area over one year and are agriculturists or relevant who use pesticides. The data collection was divided into two parts: first, population data using a questionnaire; and second, samples of environmental media including agricultural products gathered to analyze the contamination of pesticides. The data were analyzed using descriptive statistics. Findings - The most planted crop was rice (53.52 percent). Regarding agricultural chemical uses, the study found that the majority of participants used herbicides (76.83 percent). In terms of herbicide uses, Glyphosate is the most used (39.59 percent). Furthermore, insecticide consumption uses were higher in Phet Dam village than the other villages. The most common uses were Carbaryl (20.66 percent), followed by β-Betoefluthrin (15.49 percent). Originality/value - There were glyphosate and derivatives of glyphosate (Aminomethyl Phosphonic Acid) in soil and sediment samples, while herbicides and insecticides were not found in water and agricultural samples. Because these environmental contaminants are a major cause for health problems amongst producers and consumers alike, agriculturists should be supported by relevant organizations to increase organic crop cultivation methods and organic farming networks.